2019
DOI: 10.1159/000499699
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlation in Long-Term Cohort of Japanese Patients with Moyamoya Disease

Abstract: Background: Homozygosity of this p.R4810K founder variant of RNF213moyamoya disease (MMD) susceptibility gene is known to influence the severity of the clinical disease phenotype at disease onset. However, the association between this genotype and long-term clinical manifestations has remained unclear. Objectives: The principal goal of this study was to investigate whether and how the p.R4810K variant of RNF213influences the long-term phenotype in Japanese patients with MMD. Method: This retrospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 16 publications
4
21
2
Order By: Relevance
“…found that Korean patients with GA were associated with cognitive impairment in long‐term outcome . In addition, our recent study showed that patients with GA were associated with better post‐operative collateral formation , whereas p.R4810K variant was not associated with either recurrent stroke or neurological status , similar to the Japanese study .…”
Section: Discussionsupporting
confidence: 75%
“…found that Korean patients with GA were associated with cognitive impairment in long‐term outcome . In addition, our recent study showed that patients with GA were associated with better post‐operative collateral formation , whereas p.R4810K variant was not associated with either recurrent stroke or neurological status , similar to the Japanese study .…”
Section: Discussionsupporting
confidence: 75%
“…And Takahashi et al found that posterior hemorrhage was associated with a higher rate of recurrent bleeding [7]. Nevertheless, the p.R4810K variant was not associated with clinical outcomes in MMD in previous studies [18]. In present study, no difference was observed in hemorrhagic sites between two matched groups.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous study showed that patients with GA or homozygous variant (AA) may have a younger age onset, higher prevalence of family history, more cerebral infarction, and more PCA involvement. The p.R4810K variant may not relate to clinical outcomes in MMD [17,18]. Although our previous study revealed that patients with GA might associate with better postoperative collateral formation than patients with GG [12], Nomura et al found that there was no difference in recurrent strokes and functional conditions [18], our previous study also had come to the same conclusion [17].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous study showed that patients with GA or homozygous variant (AA) may have a younger age onset, higher prevalence of family history, more cerebral infarction, and more PCA involvement. The p.R4810K variant may not relate to clinical outcomes in MMD [19,20]. Although our previous study revealed that patients with GA might associate with better postoperative collateral formation than patients with GG [14], Nomura et al found that there was no difference in recurrent strokes and functional conditions [20], our previous study also had come to the same conclusion [19].…”
Section: Discussionmentioning
confidence: 54%